Getting the Most out of Social Media: Successfully Using Social Media - Lauri M. Baker; Caroline R. Warwick; Jessica C. Fernandez; Joy Rumble (EDIS, 2021)
This EDIS publication is written for Florida agriculturalists, Extension agents, agricultural organizations and other individuals interested in successfully using social media to connect with their stakeholders, potential customers or other individuals. This 3-page publication focuses on describing successful ways in which an organization can use social media and getting the most out of their social media usage. Minor revision by Lauri Baker, Caroline Warwick, Jessica Fernandez, and Joy Rumble.